FORMULATION OF SHAMPOO BAR USING ACTIVE INGREDIENTS OF CANDLENUT OIL (ALEURITES MOLUCCANUS L) AND STEARIC ACID - Fayza, Nina; Suryani, S; Elfiana, E; Fitria, F (Politeknik Negeri Lhokseumawe, 2025)
This study aimed to evaluate the effect of candlenut oil (Aleurites moluccanus L) and stearic acid ratios, along with mixing temperatures, on the quality of shampoo bars. A total of 25 formulations were prepared using five ratios of candlenut oil to stearic acid (6:30%, 11:25%, 16:20%, 21:15%, and 26:10%) and five mixing temperatures (70℃, 75℃, 80℃, 85℃, and 90℃). Constant ingredients included sodium cocoyl isethionate 41%, methyl ester sulfonate 13%, cetyl alcohol 5%, cocoa butter 1.9%, essential oil 1%, citric acid 0.1%, lexgard natural 1%, and colorant 1%. Quality evaluation referred to SNI 06-2692-1992 standards, covering pH, moisture content, foam stability, antibacterial activity, and organoleptic properties (color, aroma, texture). Results indicated that both the oil–acid ratio and mixing temperature significantly affected shampoo bar characteristics. The optimal formulation was obtained at a candlenut oil to stearic acid ratio of 6:30% with a mixing temperature of 70℃. This formula produced a pH of 6.47, stable foam with only 2.77% loss, low moisture content of 1.87%, and antibacterial activity of 100%. Organoleptic evaluation also showed high panelist acceptance for its color, aroma, and texture, indicating good consumer preference and product stability. Keywords: Shampoo Bar, Candlenut Oil, Stearic Acid, Mixing Temperature, Antibacterial